Epoxy Composite Reinforced with Bacterial Cellulose and Multi-Walled Carbon Nanotubes: Mechanical Properties and Flame Retardancy Performance - Nguyen, Tuan Anh; Nguyen, Thi Ngan (Trends in Sciences, 2025)
This study investigates the mechanical properties and flame retardancy of epoxy-based nanocomposites reinforced with bacterial cellulose (BC) and multi-walled carbon nanotubes (MWCNTs). The optimal performance was achieved with a composite containing 5 wt% BC and 0.5 wt% MWCNTs. In terms of mechanical properties, this composition exhibited superior tensile strength, flexural strength, compressive strength and impact resistance compared to other combinations. Moreover, the flame retardancy of the nanocomposite was significantly enhanced, with a limiting oxygen index (LOI) of 29.3 % and a burn rate of 16.02 mm/min. The results are attributed to the unique synergy between BC and MWCNTs, the primary components of the nanocomposite. BC, with its natural fiber structure and excellent mechanical properties, provides rigidity and strong interactions with the epoxy matrix. MWCNTs, owing to their nano-scale structure, contribute to both mechanical reinforcement and flame retardancy. This combination improves the uniformity and dispersion of the reinforcing phase within the epoxy matrix, leading to enhanced mechanical properties and flame resistance. When the BC/MWCNTs epoxy nanocomposite was further reinforced with fiberglass fabric at the optimal composition (5 wt% BC, 0.5 wt% MWCNTs), it demonstrated even higher flame retardancy, with an LOI of 30.8 % and a UL-94V rating of V1, classifying it as a highly flame-retardant material. Given these outstanding properties, the BC/MWCNTs epoxynanocomposite has potential applications not only in various industrial sectors such as aerospace, automotive and construction but also in the medical and environmental fields, where materials with high durability and flame resistance are crucial. The BC/MWCNTs material system not only demonstrates its advantages as a reinforcement in composites but also brings great prospects when fabricated into membrane form. These applications open up many new directions of development in the fields of environment, energy, biomedicine and industry, creating a solid foundation for research and practical applications. HIGHLIGHTS Optimization of Nanocomposite Composition: The epoxy composite containing 5 wt% bacterial cellulose (BC) and 0.5 wt% multi-walled carbon nanotubes (MWCNTs) achieved optimal mechanical and flame retardancy performance. Superior Mechanical Properties: The optimized composition exhibited enhanced tensile strength, flexural strength, compressive strength, and impact resistance compared to other formulations. Improved Flame Retardancy: The nanocomposite achieved a limiting oxygen index (LOI) of 29.3% and a burn rate of 16.02 mm/min, demonstrating significantly enhanced fire resistance. Synergistic Effect of BC/MWCNTs: The combination of BC’s natural fiber structure and MWCNTs’ nanoscale characteristics improved dispersion, uniformity, and overall material properties. Wide Application Potential: The material holds great promise for industries such as aerospace, automotive, and construction, as well as biomedical and environmental applications due to its high durability and excellent flame resistance. GRAPHICAL ABSTRACT